The impact of human immunodeficiency virus & acquired immunodeficiency syndrome in the Department of Agriculture : Western Cape :a human resource management planning strategy - Claasen-Hoskins, Blanche Judith (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2005.